EFFECTIVENESS OF KLUWEK SEEDS (Pangium edule) AS NATURAL PRESERVATIVES MATERIAL IN SQUID (Loligo sp.) VIEWED FROM PROTEIN PROFILE BASED ON SDS-PAGE (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Squid is a high source of protein that quickly decomposes, so efforts are needed to preserve it. One of the natural preservatives used is kluwek seeds. Kluwek contains flavonoid compounds that have antibacterial activity. This study aimed to determine the effectiveness of kluwek seeds as a natural preservative for squid in terms of protein profiles based on SDS-PAGE. The procedure begins with soaking the squid in kluwek seed suspension with concentrations of 10%, 15%, and 20% and then storing them for 24 hours. Protein content was calculated using the Bradford method and protein profiles were analyzed using the SDS-PAGE method. The molecular weight of protein bands is calculated by application GelAnalyzer 19.1. The data obtained were analyzed descriptively. The results showed that the total protein content of squid was highest at a concentration of 20% (17.86 µgµL-1), then the concentration of 15% (17.03 µgµL-1), and the lowest was the concentration of 10% (14.64 µgµL-1). Based on its protein profile, squid soaked with 20% concentration of kluwek seed suspension was the most effective for natural preservatives. This is indicated by the composition of the protein bands which are almost the same as fresh squid and protein weights ranging from 30-100 kDa. The conclusion of the research is kluwek seed suspension concentration of 20% is effective as a natural preservative for squid.
Keywords: preservatives; protein profile; Pangium edule